1995
DOI: 10.1073/pnas.92.17.7986
|View full text |Cite
|
Sign up to set email alerts
|

Role of pili and the phase-variable PilC protein in natural competence for transformation of Neisseria gonorrhoeae.

Abstract: The Gram-negative bacterial pathogen Neisseria gonorrhoeae is naturally competent for transformation with species-related DNA. We show here that two phasevariable pilus-associated proteins, the major pilus subunit (pilin, or PilE) and PilC, a factor known to function in the assembly and adherence of gonococcal pili, are essential for transformation competence. The PilE and PilC proteins are necessary for the conversion of linearized plasmid DNA carrying the Neisseria-specific DNA uptake signal into a DNase-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 32 publications
2
100
0
Order By: Relevance
“…These results support the notion that the binding of DNA to ComE is not sequence specific. Strains with mutations of pilC, whose product is a pilus tip adhesin (35), are impaired in their ability to take up DNA and undergo transformation; competence could be partially restored in these mutants by supplying them with exogenous purified PilC (34). We tested rComE in a similar way and found that exogenously added ComE did not restore the transformation ability of comE mutant bacteria (data not shown).…”
Section: Vol 183 2001mentioning
confidence: 93%
See 1 more Smart Citation
“…These results support the notion that the binding of DNA to ComE is not sequence specific. Strains with mutations of pilC, whose product is a pilus tip adhesin (35), are impaired in their ability to take up DNA and undergo transformation; competence could be partially restored in these mutants by supplying them with exogenous purified PilC (34). We tested rComE in a similar way and found that exogenously added ComE did not restore the transformation ability of comE mutant bacteria (data not shown).…”
Section: Vol 183 2001mentioning
confidence: 93%
“…Neisseria has type IV pili (TFP), and it was early observed that piliation is necessary for DNA uptake (3), but it is still not known whether pili themselves participate in the process, since DNA-binding activity has not been detected in pilus components (26). Among the genes known to be necessary for competence are those encoding components of the TFP, such as pilE (pilin) and pilC (tip adhesin) (34), and those encoding proteins involved in pilus biogenesis (pilD, pilG, pilF, and pilQ) or function, such as twitching motility (pilT) (10,14,42,44). Mutations in these genes result in the absence of pili or in nonfunctional pili.…”
mentioning
confidence: 99%
“…The DNA transformation systems of B. subtilis and H. influenzae, microorganisms which have never been found to exhibit type IV pilus structures, contain components similar to proteins implicated in type IV pilus biogenesis in other organisms (5,20,40). In N. gonorrhoeae, which exhibits a type IV piliation phenotype, the structural subunits of type IV pili (PilE) and the type IV pilus factor PilC are essential for DNA transformation (7,35). Furthermore it was demonstrated that gonococcal PilT mutants exhibit simultaneous defects in competence for natural transformation and twitching motility (43).…”
Section: Discussionmentioning
confidence: 99%
“…3). Interestingly, while the presence of pili on the bacterial surface per se may not be required for DNA uptake, production of the major pilin is necessary (91,206,382,509,562). These findings suggest that some (but not all) components of T4P are involved in DNA uptake (141,142,189,509,602,644).…”
Section: Dna Uptake and Processingmentioning
confidence: 99%
“…T4P are hair-like appendages found on the bacterial surface that mediate cellular adhesion and twitching motility, which is a form of bacterial translocation due to polymerization or extension of the pilus fiber, attachment to a nearby surface, and then depolymerization or retraction of the pilus (112,404,417,543,621). T4P are composed of a major pilin (PilE), a minor pilin (PilV), a traffic NTPase (PilT), an ATPase (PilF), a transmembrane secretin (PilQ), a prepilin processing peptidase (PilD), a pilot protein (PilP), and an adhesin (PilC) (1,27,57,59,66,91,141,189,295,342,509,602,644) (Fig. 3).…”
Section: Dna Uptake and Processingmentioning
confidence: 99%